2010
DOI: 10.1016/j.ejphar.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

The glial cell modulator and phosphodiesterase inhibitor, AV411 (ibudilast), attenuates prime- and stress-induced methamphetamine relapse

Abstract: Stress and renewed contact with drug (a “slip”) have been linked to persisting relapse of methamphetamine abuse. Human brain microglial activation has been linked with methamphetamine abuse, and inhibitors of glial cell activation, certain phosphodiesterase (PDE) inhibitors, and glial cell derived neurotrophic factor (GDNF) have been reported to modulate drug abuse effects. Our objective was to determine whether the glial cell attenuator, 3-isobutyryl-2-isopropylpyrazolo-[1,5-a]pyridine (AV411, ibudilast), a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 63 publications
2
65
1
Order By: Relevance
“…To date, the research by Beardsley and colleagues has provided some of the best preclinical evidence for the potential utility of ibudilast in treatment of methamphetamine abuse and relapse (Beardsley et al, 2010;Snider et al, 2013). For example, Snider et al (2013) found that 7.5 and 10 mg/kg ibudilast attenuated methamphetamine intake.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, the research by Beardsley and colleagues has provided some of the best preclinical evidence for the potential utility of ibudilast in treatment of methamphetamine abuse and relapse (Beardsley et al, 2010;Snider et al, 2013). For example, Snider et al (2013) found that 7.5 and 10 mg/kg ibudilast attenuated methamphetamine intake.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown the potential of this drug in reducing neuroinflammation in a number of neurological conditions such as relapsing-remitting multiple sclerosis (Barkhof et al, 2010), Tat-induced neurotoxicity (Kiebala and Maggirwar, 2011), potentiation of opioid analgesia (Hutchinson et al, 2009), and attenuation of methamphetamine-taking and relapse in animal models (Beardsley et al, 2010;Snider et al, 2013). At present, it is unknown how ibudilast impacts the synapse-a key structure involved in neurotransmission and neuroplasticity.…”
Section: Introductionmentioning
confidence: 98%
“…Ibudilast, commonly used in the treatment of asthma, inhibits PDE activity and possesses anti-inflammatory and neuroprotective effects (Rolan et al, 2009). Systemic administration of ibudilast inhibits ethanol (Bell et al, 2015) and methamphetamine intake (Snider et al, 2013), sensitization of the locomotor response to methamphetamine (Snider et al, 2012), as well as stress-and drug-primed reinstatement of methamphetamine seeking (Beardsley et al, 2010). Ibudilast also reduces morphine withdrawal and CPP, likely as a result of its ability to reduce morphine-induced dopamine release in the NAc (Rolan et al, 2009;Schwarz and Bilbo, 2013).…”
Section: G Glial Modulatorsmentioning
confidence: 99%
“…In the MA-reinstatement model, rats were trained to lever press for MA after which MA infusions were discontinued and lever pressing extinguished. IBUD significantly reduced MA prime-and stress-induced reinstatement of active lever pressing (Beardsley, Shelton, Hendrick, & Johnson, 2010) suggesting that IBUD may be effective in reducing relapse during clinical treatment for MA dependence. While both high and low IBUD doses reduced stress-induced reinstatement, only the higher IBUD dose reduced prime-induced reinstatement.…”
Section: Continuedmentioning
confidence: 85%